Healthy-minded religious phenomenon in shalawatan: a study on the three majelis shalawat in Java - Sekar Ayu Aryani (Indonesian Journal of Islam and Muslim Societies, 2017)
As a movement, majelis shalawat becomes religious phenomenon that recently flourish in Indonesia, particularly Java. It emerges as urban spirituality like majelis dzikir that previously popular among people. However majelis shalawat is dissimilar with majelis dzikir due to its characters are not sadness, sorrow, and crying; it prefer to express happiness, cheerful, and enjoying religion. These characters indicate a Healthy-minded religious phenomenon, a term which is came  originally from William James and popularized by W.H.Clark. Among many majelis shalawat groups ini Indonesia, the three most famous and biggest are Majelis Shalawat Habib Syech (Surakarta), Habib Luthfi (Pekalongan), and Maiyah Cak Nun (Yogyakarta). This research explores characteristics of majelis shalawat that indicate healthy-mindedness. Furthermore, it also discovers various motivations that lead people (jamaah) to follow the majelis shalawat. Conducting qualitative method and Psychology of Religion approach, and employing interview and observation as method for data gathering, it results several findings. First, as a religious activity, shalawatan reallydepends on the role of its charismatic leader. The charisma of Habib Luthfi, Habib Syech, and Cak Nun is the main attractive factor for jamaah to come. It ; " is because the charismatic leaders have deep understanding of religious knowledge and they also are blessed with certain talent such as beautiful voice and having good skill on music. Besides that, the leaders are often giving smart joke. Second, through shalawatan, people feel happiness and optimistic to face their life, preferring extrovert attitudes, have more free theology, and feels conducive atmosphere for their religious growth. Those are evidences that majelis shalawat has healthy-mindedness characters. Third, people motivation also in in attending majlis shalawat consist of religious escapism, strengthening solidarity and ukhuwah islamiyah, to learn more religious knowledge (thalabul ‘ilmi), and to gain religious transformation.Majelis shalawat sebagai sebuah gerakan merupakan fenomena keagamaan yang marak di Indonesia khususnya Jawa. Kehadirannya lebih sebagai spiritualitas urban namun tampil berbeda jika dibandingkan majelis dzikir yang terlebih dahulu populer. Majelis shalawat tidak menunjukkan cirri sendu, muram, dan tangisan seperti majelis dzikir, namun justru memperlihatkan cirri bahagia, senang, dan menikmati agama. Karakteristik beragama yang demikian oleh Clark dan William James disebut healthy mindedness. Dari beberapa majelis shalawat di Indonesia, tiga yang terbesar adalah Majelis Shalawat Habib Syech (Surakarta), Habib Luthfi (Pekalongan), Maiyah Cak Nun (Yogyakarta). Penelitian ini menelusuri apa saja karakteristik majelis shalawat yang merupakan indikasi healthymindedness, kemudian mengungkap pula ragam motivasi yang mendorong jamaah mengikuti majelis shalawat. Dengan menerapkan metode kualitatif dan pendekatan Psikologi Agama, dan dengan interview serta observasi sebagai alat utama pengumpulan data, penelitian ini menghasilkan beberapa temuan. Pertama, sebagai sebuah aktifitas keagamaan, majelis shalawat cukup bergantung dari peran sang tokoh utama pemimpin majelis shalawat. Karisma Habib Luthfi, Habib Syech, dan Cak Nun merupakan daya tarik terbesar bagi jamaah. Hal ini karena selain memiliki kedalaman ilmu agama, para pemimpin karismatik tersebut juga diberkahi dengan kemerduan suara dan kemampuan bermusik, bahkan humor cerdas juga sering muncul sehingga menjadi daya tarik tersendiri bagi jamaah. Kedua, dengan mengikuti majeliss halawat, jamaah merasakan kebahagiaan dan optimism dalam menatap kehidupan, mereka bersikap lebih ekstrovet, berteologi secara lebih bebas, dan merasakan situasi yang mendukung untuk perkembangan keberagamaan mereka. Hal-hal tersebut menandakan bahwa majelis shalawat memiliki karakter healthy-mindedness. Ketiga, motivasi jamaah dalam mengikuti majlis shalawat, yaitu untuk mendapatkan jalan keluar yang agamis, menguatkansilaturahim dan ukhuwah islamiyah, mencari ilmu(thalabul ‘ilmi), dan untukmencapai transformasi keagamaan.